FORMS OF THE EXPRESSION OF MOTION IN ENGLISH AND UZBEK: A LEXICAL-SEMANTIC APPROACH (International journal of artificial intelligence, 2026)
This article examines the lexical-semantic characteristics of forms of motion in English and Uzbek. The study of how motion is expressed in language is one of the significant linguistic issues, since each language has its own unique ways of representing action, direction, manner of motion, as well as its duration and repetition. A comparative linguistic analysis of these features is carried out using examples from both languages.